Use of the GenoType® MTBDRplus assay to assess drug resistance of Mycobacterium tuberculosis isolates from patients in rural Uganda - Bazira, Joel; Asiimwe, Benon B; Joloba, Moses L; Bwanga, Fred; Matee, Mecky I (BMC clinical pathology, 2010)
Background: Drug resistance levels and patterns among Mycobacterium tuberculosis isolates from newly diagnosed and previously treated tuberculosis patients in Mbarara Uganda were investigated. Methods: We enrolled, consecutively, all newly diagnosed and previously treated smear-positive TB patients aged ≥ 18 years. Isolates were tested for drug resistance against rifampicin (RIF) and isoniazid (INH) using the Genotype® MDRTBplus assay and results were compared with those obtained by the indirect proportion method on Lowenstein-Jensen media. HIV testing was performed using two rapid HIV tests. Results: A total of 125 isolates from 167 TB suspects with a mean age 33.7 years and HIV prevalence of 67.9% (55/81) were analysed. A majority (92.8%) of the participants were newly presenting while only 7.2% were retreatment cases. Resistance mutations to either RIF or INH were detected in 6.4% of the total isolates. Multidrug resistance, INH and RIF resistance was 1.6%, 3.2% and 4.8%, respectively. The rpob gene mutations seen in the sample were D516V, S531L, H526Y H526 D and D516V, while one strain had a Δ1 mutation in the wild type probes. There were three strains with katG (codon 315) gene mutations while only one strain showed the inhA promoter region gene mutation. Conclusion: The TB resistance rate in Mbarara is relatively low. The GenoType® MTBDRplus assay can be used for rapid screening of MDR-TB in this setting
Keywords: GenoType®; Drug resistance; MTBDRplus assay; Mycobacterium tuberculosis; Patients; Uganda